The design analysis handbook : a practical guide to design validation - Walker, N. Edward (Newnes, 1998)
" ... A book that should be on the shelf of every digital or analog electronic-system designer."--Frank Goodenough, Electronic Design This Handbook offers design engineers and managers immediately useful, meat-and-potatoes techniques for achieving design validation by analysis in an easy-to-read style. The book contains numerous useful and interesting tips for electronics circuit designers. Examples of rectifier circuits, power supplies, digital timing, thermal analysis, grounding and layout, and EMI/noise control are examined in detail with fully worked-out numerical examples. If you need to create reliable, cost-effective, optimized designs, The Design Analysis Handbook provides a practical framework for integrating quality into the design process from start to finish. The methodology used is called Worst Case Analysis Plus (WCA+), a design-validation tool that demands thoroughness and analytical thinking by the user. A guide to assessing and validating circuit design, The Design Analysis Handbook presents processes and mathematical tools in a straightforward, real-world manner. Unique features of the approach include chapters on safety, bad science, and surviving high-pressure design projects. N. Edward Walker is the president of Design/Analysis Consultants, Inc., based in Tampa, Florida. The Handbook is based on DACI's extensive experience in the design and analysis of highly-reliable electronic systems. Straightforward guide to practical design validation Shows how to avoid design hazards Provides framework for integrating quality with the design process
Keywords: Engineering design.; Quality control.; Electronic circuit design.; Reliability (Engineering); elektronické knihy; electronic books